Egg Shells as an Adsorbent for the Adsorption of Lead (Pb) and Iron (Fe) Metals - Yusmartini, Eka Sri Yusmartini; Mardwita, Mardwita; Atikah, Atikah; Kaswari, Suli Cahaya (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
An eggshell is estimated to have around 10,000–20,000 pores; this condition created a chance for the eggshells to be used as an adsorbent. This research aims to activate egg shells used as an adsorbent. Egg shells were applied as an adsorbent in solutions of lead (Pb) and iron (Fe). Test parameters for adsorption capacity were carried out on the optimum mass and absorption contact time with lead (Pb) and iron (Fe) while using the eggshell waste as an adsorbent. The adsorbent quality of egg shells was tested using parameters such as ash content, water content, and adsorption capacity towards methyl blue. This research aims to utilize egg shells as an adsorbent to absorb lead (Pb) and iron (Fe) content using an adsorption process. There are 3 stages of a method for this research to establish: adsorbent preparation, adsorbent activation, and the adsorption process. The adsorption process was carried out with variations of the mass sample, which are 0.75 grams, 1 gram, 1.25 grams, 1.50 grams, and 2 grams and time variations when contact occurred in 20, 30, 40, 50, and 60 minutes. The outcome of this research showed that the highest adsorption capacity at the optimum mass of Pb metal was 1.5 grams at 98.914% and for Fe metal at 96.386%. The highest adsorption capacity results were influenced by Pb metal contact time in 40 minutes, which was 99.30%, and the best capacity for adsorption of Fe metal was at a contact time in 50 minutes, which was 99.82%.